Kategori dan Fungsi Majas dalam Lirik Lagu Album Bintang Lima Dewa 19 - Aprianti, Annika; Thahar, Harris Effendi; Zulfadhli, Zulfadhli (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this research is (1) describing the kind of figurative of speech lyric Dewa 19 song at Bintang Limaalbum, (2) stating the dominance figurative of speech in Dewa 19 song at Bintang Lima album, (3) describing the function of figurative of speech lyric in Dewa 19 song at Bintang Lima album. The research data is Dewa 19 song at Bintang Lima album. The resources of this research is song lyric. The collection of data by reading song lyric, pointing the sentence that using figurative of speech, to predict the function of figurative of speech. The result is 13 figurative of speech, the dominance is repetitive figurative of speech about 17 and figurative of speech function about 4 that is concreting, alleviating, empasizhing and to beautify.